Aberrant DNA hypermethylation of SDHC: a novel mechanism of tumor development in Carney triad - Haller, Florian; Moskalev, Evgeny; Faucz, Fabio R.; Barthelmeß, Sarah; Wiemann, Stefan; Bieg, Matthias; Assie, Guillaume; Bertherat, Jerome; Schaefer, Inga-Marie; Otto, Claudia; Rattenberry, Eleanor; Maher, Eamonn R.; et al. (Endocrine-Related Cancer, 2014)
Carney triad (CT) is a rare condition with synchronous or metachronous occurrence of gastrointestinal stromal tumors (GISTs), paragangliomas (PGLs), and pulmonary chondromas in a patient. In contrast to Carney-Stratakis syndrome (CSS) and familial PGL syndromes, no germline or somatic mutations in the succinate dehydrogenase (SDH) complex subunits A, B, C, or D have been found in most tumors and/or patients with CT. Nonetheless, the tumors arising among patients with CT, CSS, or familial PGL share a similar morphology with loss of the SDHB subunit on the protein level. For the current study, we employed massive parallel bisulfite sequencing to evaluate DNA methylation patterns in CpG islands in proximity to the gene loci of all four SDH subunits. For the first time, we report on a recurrent aberrant dense DNA methylation at the gene locus of SDHC in tumors of patients with CT, which was not present in tumors of patients with CSS or PGL, or in sporadic GISTs with KIT mutations. This DNA methylation pattern was correlated to a reduced mRNA expression of SDHC, and concurrent loss of the SDHC subunit on the protein level. Collectively, these data suggest epigenetic inactivation of the SDHC gene locus with functional impairment of the SDH complex as a plausible alternate mechanism of tumorigenesis in CT.
EVALuna2:6647

Benchmarking whole exome sequencing in the German network for personalized medicine - Menzel, Michael; Martis-Thiele, Mihaela; Goldschmid, Hannah; Ott, Alexander; Romanovsky, Eva; Siemanowski-Hrach, Janna; Seillier, Lancelot; Brüchle, Nadina Ortiz; Maurer, Angela; Lehmann, Kjong Van; Begemann, Matthias; Elbracht, Miriam; et al. (European Journal of Cancer, 2024)
Introduction: Whole Exome Sequencing (WES) has emerged as an efficient tool in clinical cancer diagnostics to broaden the scope from panel-based diagnostics to screening of all genes and enabling robust determination of complex biomarkers in a single analysis. Methods: To assess concordance, six formalin-fixed paraffin-embedded (FFPE) tissue specimens and four commercial reference standards were analyzed by WES as matched tumor-normal DNA at 21 NGS centers in Germany, each employing local wet-lab and bioinformatics. Somatic and germline variants, copy-number alterations (CNAs), and complex biomarkers were investigated. Somatic variant calling was performed in 494 diagnostically relevant cancer genes. The raw data were collected and re-analyzed with a central bioinformatic pipeline to separate wet- and dry-lab variability. Results: The mean positive percentage agreement (PPA) of somatic variant calling was 76 % while the positive predictive value (PPV) was 89 % in relation to a consensus list of variants found by at least five centers. Variant filtering was identified as the main cause for divergent variant calls. Adjusting filter criteria and re-analysis increased the PPA to 88 % for all and 97 % for the clinically relevant variants. CNA calls were concordant for 82 % of genomic regions. Homologous recombination deficiency (HRD), tumor mutational burden (TMB), and microsatellite instability (MSI) status were concordant for 94 %, 93 %, and 93 % of calls, respectively. Variability of CNAs and complex biomarkers did not decrease considerably after harmonization of the bioinformatic processing and was hence attributed mainly to wet-lab differences. Conclusion: Continuous optimization of bioinformatic workflows and participating in round robin tests are recommended.
CRIS-Team Scopus Importer:2024-09-27
Keywords: Clinical exome; Molecular pathology; Multi-centric inter-laboratory test; Precision oncology; Whole exome sequencing

BiasCorrector: Fast and accurate correction of all types of experimental biases in quantitative DNA methylation data derived by different technologies - Kapsner, Lorenz; Zavgorodnij, Mikhail G.; Majorova, Svetlana P.; Hotz-Wagenblatt, Agnes; Kolychev, Oleg V.; Lebedev, Igor N.; Hoheisel, Jörg D.; Hartmann, Arndt; Bauer, Andrea; Mate, Sebastian; Prokosch, Hans-Ulrich; Haller, Florian; et al. (International Journal of Cancer, 2021)
Quantification of DNA methylation in neoplastic cells is crucial both from mechanistic and diagnostic perspectives. However, such measurements are prone to different experimental biases. Polymerase chain reaction (PCR) bias results in an unequal recovery of methylated and unmethylated alleles at the sample preparation step. Post-PCR biases get introduced additionally by the readout processes. Correcting the biases is more practicable than optimising experimental conditions, as demonstrated previously. However, utilisation of our earlier developed algorithm strongly necessitates automation. Here, we present two R packages: rBiasCorrection, the core algorithms to correct biases; and BiasCorrector, its web-based graphical user interface frontend. The software detects and analyses experimental biases in calibration DNA samples at a single base resolution by using cubic polynomial and hyperbolic regression. The correction coefficients from the best regression type are employed to compensate for the bias. Three common technologies—bisulphite pyrosequencing, next-generation sequencing and oligonucleotide microarrays—were used to comprehensively test BiasCorrector. We demonstrate the accuracy of BiasCorrector's performance and reveal technology-specific PCR- and post-PCR biases. BiasCorrector effectively eliminates biases regardless of their nature, locus, the number of interrogated methylation sites and the detection method, thus representing a user-friendly tool for producing accurate epigenetic results.
CRIS-Team Scopus Importer:2021-06-04
Keywords: BiasCorrector; cancer; DNA methylation; PCR-bias; post-PCR bias

Combined DNA methylation and gene expression profiling in gastrointestinal stromal tumors reveals hypomethylation of SPP1 as an independent prognostic factor - Haller, Florian; Zhang, Jitao David; Moskalev, Evgeny; Braun, Alexander; Otto, Claudia; Geddert, Helene; Riazalhosseini, Yasser; Ward, Aoife; Balwierz, Aleksandra; Schaefer, Inga-Marie; Cameron, Silke; Ghadimi, B. Michael; et al. (International Journal of Cancer, 2015)
Gastrointestinal stromal tumors (GISTs) have distinct gene expression patterns according to localization, genotype and aggressiveness. DNA methylation at CpG dinucleotides is an important mechanism for regulation of gene expression. We performed targeted DNA methylation analysis of 1.505 CpG loci in 807 cancer-related genes in a cohort of 76 GISTs, combined with genome-wide mRNA expression analysis in 22 GISTs, to identify signatures associated with clinicopathological parameters and prognosis. Principal component analysis revealed distinct DNA methylation patterns associated with anatomical localization, genotype, mitotic counts and clinical follow-up. Methylation of a single CpG dinucleotide in the non-CpG island promoter of SPP1 was significantly correlated with shorter disease-free survival. Hypomethylation of this CpG was an independent prognostic parameter in a multivariate analysis compared to anatomical localization, genotype, tumor size and mitotic counts in a cohort of 141 GISTs with clinical follow-up. The epigenetic regulation of SPP1 was confirmed in vitro, and the functional impact of SPP1 protein on tumorigenesis-related signaling pathways was demonstrated. In summary, SPP1 promoter methylation is a novel and independent prognostic parameter in GISTs, and might be helpful in estimating the aggressiveness of GISTs from the intermediate-risk category.
EVALuna2:6650

Comparative analysis of tumour mutational burden (TMB) prediction methods and its association with determinants of the tumour immune microenvironment of urothelial bladder cancer (UBC) - Eckstein, Markus; Hartmann, Arndt; Strissel, Pamela; Strick, Reiner; Wach, S.; Taubert, Helge; Wullich, Bernd; Geppert, Carol-Immanuel; Weyerer, Veronika; Stöhr, Robert; Rübner, Matthias; Fasching, Peter; et al. (ANNALS OF ONCOLOGY, 2019)
CRIS-Team WoS Importer:2019-11-08

Determinants Affecting the Clinical Implementation of a Molecularly Informed Molecular Tumor Board Recommendation: Experience from a Tertiary Cancer Center. - Tögel, Lars; Schubart, Christoph; Lettmaier, Sebastian; Neufert, Clemens; Hoyer, Juliane; Wolff, Kerstin; Moskalev, Evgeny; Stöhr, Robert; Agaimy, Abbas; Wiesmann da Silva Reis, André; Wullich, Bernd; Mackensen, Andreas; et al. (Cancers, 2023)
Molecular Tumor Boards (MTBs) converge state-of-the-art next-generation sequencing (NGS) methods with the expertise of an interdisciplinary team consisting of clinicians, pathologists, human geneticists, and molecular biologists to provide molecularly informed guidance in clinical decision making to the treating physician. In the present study, we particularly focused on elucidating the factors impacting on the clinical translation of MTB recommendations, utilizing data generated from gene panel mediated comprehensive genomic profiling (CGP) of 554 patients at the MTB of the Comprehensive Cancer Center Erlangen, Germany, during the years 2016 to 2020. A subgroup analysis of cases with available follow-up data (n = 332) revealed 139 cases with a molecularly informed MTB recommendation, which was successfully implemented in the clinic in 44 (31.7%) of these cases. Here, the molecularly matched treatment was applied in 45.4% (n = 20/44) of cases for ≥6 months and in 25% (n = 11/44) of cases for 12 months or longer (median time to treatment failure, TTF: 5 months, min: 1 month, max: 38 months, ongoing at data cut-off). In general, recommendations were preferentially implemented in the clinic when of high (i.e., tier 1) clinical evidence level. In particular, this was the case for MTB recommendations suggesting the application of PARP, PIK3CA, and IDH1/2 inhibitors. The main reason for non-compliance to the MTB recommendation was either the application of non-matched treatment modalities (n = 30)/stable disease (n = 7), or deteriorating patient condition (n = 22)/death of patient (n = 9). In summary, this study provides an insight into the factors affecting the clinical implementation of molecularly informed MTB recommendations, and careful considerations of these factors may guide future processes of clinical decision making.
EVALuna2:545872
Keywords: Molecular Tumor Board; clinical decision making; precision medicine; molecular pathology; real-world data; cancer care

Distinct genetic alterations and luminal molecular subtype in nested variant of urothelial carcinoma - Weyerer, Veronika; Weisser, Rebecca; Moskalev, Evgeny; Haller, Florian; Stöhr, Robert; Eckstein, Markus; Zinnall, Ulrike; Gaisa, Nadine T.; Comperat, Eva; Perren, Aurel; Keck, Bastian; Allory, Yves; et al. (Histopathology, 2019)
Aims Nested variant of urothelial carcinoma (NVUC) is rare, and only a few small series exist. Molecular characteristics and the classifying marker profile as well as therapeutic targets of this specific variant are mostly unknown. The aim of this study was to characterise NVUC at the molecular level in one of the largest cohorts to date. In addition, we applied an immunohistochemical marker panel in order to define the molecular subtype. Methods and results Sixty NVUC cases were collected from different departments. TERT promoter mutation analysis was carried out in all samples using SNaPshot analysis. Targeted sequencing of 48 cancer-related genes by next-generation sequencing (NGS) analysis was performed in a subset of 26 cases. Immunohistochemical markers CD44, CK5, CK14, EGFR, p63, FOXA1, GATA3, CD24 and CK20 were used to elucidate the molecular subtype. A total of 62.5% of NVUC cases harboured a mutation of the TERT promoter. Additionally, TP53, JAK3 and CTNNB1 were among the most frequently mutated genes identified by NGS analysis. Subtyping revealed that all NVUC express luminal markers such as CD24, FOXA1, GATA3 and CK20. Conclusions In summary, NVUC belong to the luminal molecular subtype. Moreover, a subset of NVUC seems to be characterised by mutations of the Wnt and inflammatory pathways, including JAK3 mutations, indicating a different biological background compared to conventional urothelial bladder cancer.
CRIS-Team WoS Importer:2019-11-01

Distinct genetic alterations and luminal molecular subtype in nested variant of urothelial carcinoma - Weyerer, Veronika; Weisser, R.; Moskalev, Evgeny; Haller, Florian; Stoehr, R.; Eckstein, Markus; Zinnall, U.; Gaisa, N. T.; Comperat, E.; Perren, A.; Keck, Bastian; Allory, Y.; et al. (Virchows Archiv, 2019)
CRIS-Team WoS Importer:2019-09-27

DNA-methylation signature accurately differentiates pancreatic cancer from chronic pancreatitis in tissue and plasma - Wu, Yenan; Seufert, Isabelle; Al-Shaheri, Fawaz N.; Kurilov, Roman; Bauer, Andrea S.; Manoochehri, Mehdi; Moskalev, Evgeny; Brors, Benedikt; Tjaden, Christin; Giese, Nathalia A.; Hackert, Thilo; Büchler, Markus W.; et al. (Gut, 2023)
Objective: Pancreatic ductal adenocarcinoma (PDAC) is a lethal malignancy. Differentiation from chronic pancreatitis (CP) is currently inaccurate in about one-third of cases. Misdiagnoses in both directions, however, have severe consequences for patients. We set out to identify molecular markers for a clear distinction between PDAC and CP. Design: Genome-wide variations of DNA-methylation, messenger RNA and microRNA level as well as combinations thereof were analysed in 345 tissue samples for marker identification. To improve diagnostic performance, we established a random-forest machine-learning approach. Results were validated on another 48 samples and further corroborated in 16 liquid biopsy samples. Results: Machine-learning succeeded in defining markers to differentiate between patients with PDAC and CP, while low-dimensional embedding and cluster analysis failed to do so. DNA-methylation yielded the best diagnostic accuracy by far, dwarfing the importance of transcript levels. Identified changes were confirmed with data taken from public repositories and validated in independent sample sets. A signature of six DNA-methylation sites in a CpG-island of the protein kinase C beta type gene achieved a validated diagnostic accuracy of 100% in tissue and in circulating free DNA isolated from patient plasma. Conclusion: The success of machine-learning to identify an effective marker signature documents the power of this approach. The high diagnostic accuracy of discriminating PDAC from CP could have tremendous consequences for treatment success, once the result from still a limited number of liquid biopsy samples would be confirmed in a larger cohort of patients with suspected pancreatic cancer.
CRIS-Team Scopus Importer:2023-10-06
Keywords: chronic pancreatitis; pancreatic cancer

Early Epigenetic Downregulation of microRNA-192 Expression Promotes Pancreatic Cancer Progression - Botla, Sandeep K.; Savant, Soniya; Jandaghi, Pouria; Bauer, Andrea S.; Muecke, Oliver; Moskalev, Evgeny; Neoptolemos, John P.; Costello, Eithne; Greenhalf, William; Scarpa, Aldo; Gaida, Matthias M.; Buechler, Markus W.; et al. (Cancer Research, 2016)
Pancreatic ductal adenocarcinoma (PDAC) is characterized by very early metastasis, suggesting the hypothesis that metastasis-associated changes may occur prior to actual tumor formation. In this study, we identified miR-192 as an epigenetically regulated suppressor gene with predictive value in this disease. miR-192 was downregulated by promoter methylation in both PDAC and chronic pancreatitis, the latter of which is a major risk factor for the development of PDAC. Functional studies in vitro and in vivo in mouse models of PDAC showed that overexpression of miR-192 was sufficient to reduce cell proliferation and invasion. Mechanistic analyses correlated changes in miR-192 promoter methylation and expression with epithelial-mesenchymal transition. Cell proliferation and invasion were linked to altered expression of the miR-192 target gene SERPINE1 that is encoding the protein plasminogen activator inhibitor-1 (PAI-1), an established regulator of these properties in PDAC cells. Notably, our data suggested that invasive capacity was altered even before neoplastic transformation occurred, as triggered by miR-192 downregulation. Overall, our results highlighted a role for miR-192 in explaining the early metastatic behavior of PDAC and suggested its relevance as a target to develop for early diagnostics and therapy. Cancer Res; 76(14); 4149-59. ©2016 AACR.
EVALuna2:6829

EGFR Mutation Testing Using Liquid Biopsy Technology for Patients with Advanced EGFR-Mutant NSCLC - Seitz, Jan; Moskalev, Evgeny; Fuchs, Florian; Haller, Florian; Hartmann, Arndt (2018)
EVALuna2:34073

Enhancer hijacking activates oncogenic transcription factor NR4A3 in acinic cell carcinomas of the salivary glands - Haller, Florian; Bieg, Matthias; Will, Rainer; Koerner, Cindy; Weichenhan, Dieter; Bott, Alexander; Ishaque, Naveed; Lutsik, Pavlo; Moskalev, Evgeny; Müller, Susanna; Baehr, Marion; Woerner, Angelika; et al. (Nature Communications, 2019)
The molecular pathogenesis of salivary gland acinic cell carcinoma (AciCC) is poorly understood. The secretory Ca-binding phosphoprotein (SCPP) gene cluster at 4q13 encodes structurally related phosphoproteins of which some are specifically expressed at high levels in the salivary glands and constitute major components of saliva. Here we report on recurrent rearrangements [t(4;9)(q13;q31)] in AciCC that translocate active enhancer regions from the SCPP gene cluster to the region upstream of Nuclear Receptor Subfamily 4 Group A Member 3 (NR4A3) at 9q31. We show that NR4A3 is specifically upregulated in AciCCs, and that active chromatin regions and gene expression signatures in AciCCs are highly correlated with the NR4A3 transcription factor binding motif. Overexpression of NR4A3 in mouse salivary gland cells increases expression of known NR4A3 target genes and has a stimulatory functional effect on cell proliferation. We conclude that NR4A3 is upregulated through enhancer hijacking and has important oncogenic functions in AciCC.
EVALuna2:35381

Epigenetic Regulation of CD133 in Gastrointestinal Stromal Tumors - Geddert, Helene; Braun, Alexander; Kayser, Claudia; Dimmler, Arno; Faller, Gerhard; Agaimy, Abbas; Haller, Florian; Moskalev, Evgeny (American Journal of Clinical Pathology, 2017)
This study ascertained the regulation of the stem cell marker CD133 and its potential applicability for prognostication of gastrointestinal stromal tumors (GISTs).A total of 95 resected GISTs were included in the study. CD133 protein expression was assessed immunohistochemically on tissue microarrays. Methylation percentage was quantified by pyrosequencing. Gene expression in cell lines GIST48b and GIST882 upon treatment with DNA demethylation agent 5-aza-2'-deoxycytidine was analyzed by quantitative polymerase chain reaction.The expression of hypermethylated CD133 could be reactivated in the GIST cell line upon hypomethylation with the drug. Similarly, in patient material, CD133 methylation percentage correlated inversely with the protein expression and reflected tumor size with hypermethylation in small (<2 cm) tumors and virtually no methylation in large (>10 cm) GISTs. The gene's methylation percentage and expression level were clearly specific to anatomic sites and distinct driver mutations. KIT -mutant gastric GISTs exhibited significantly lower methylation degrees and concomitant high CD133 protein abundance compared with KIT -mutant GISTs from the small intestine. CD133 hypermethylation was documented in PDGFRA -mutant gastric GISTs along with low CD133 expression compared with KIT -mutant gastric GISTs. High CD133 expression was a prognosticator of shorter disease-free survival in all patients. In a subgroup of KIT -mutant gastric GISTs, low CD133 methylation degree was correlated with a shorter disease-free survival.Our results strongly suggest epigenetic regulation of CD133 expression by promoter methylation in GISTs. Pending further validation studies, high abundance of the protein can serve as a marker for malignant GISTs.
EVALuna2:6853

Gene Expression in Solitary Fibrous Tumors (SFTs) Correlates with Anatomic Localization and NAB2-STAT6 Gene Fusion Variants - Bieg, Matthias; Moskalev, Evgeny; Will, Rainer; Hebele, Simone; Schwarzbach, Matthias; Schmeck, Sanja; Hohenberger, Peter; Jakob, Jens; Kasper, Bernd; Gaiser, Timo; Ströbel, Philip; Wardelmann, Eva; et al. (American Journal of Pathology, 2021)
Solitary fibrous tumors (SFTs) harbor recurrent NAB2-STAT6 gene fusions, promoting constitutional up-regulation of oncogenic early growth response 1 (EGR1)-dependent gene expression. SFTs with the most common canonical NAB2 exon 4–STAT6 exon 2 fusion variant are often located in the thorax (pleuropulmonary) and are less cellular with abundant collagen. In contrast, SFTs with NAB2 exon 6–STAT6 exon 16/17 fusion variants typically display a cellular round to ovoid cell morphology and are often located in the deep soft tissue of the retroperitoneum and intra-abdominal pelvic region or in the meninges. Here, we employed next-generation sequencing–based gene expression profiling to identify significant differences in gene expression associated with anatomic localization and NAB2-STAT6 gene fusion variants. SFTs with the NAB2 exon 4–STAT6 exon 2 fusion variant showed a transcriptional signature enriched for genes involved in DNA binding, gene transcription, and nuclear localization, whereas SFTs with the NAB2 exon 6–STAT6 exon 16/17 fusion variants were enriched for genes involved in tyrosine kinase signaling, cell proliferation, and cytoplasmic localization. Specific transcription factor binding motifs were enriched among differentially expressed genes in SFTs with different fusion variants, implicating co–transcription factors in the modification of chimeric NGFI-A binding protein 2 (NAB2)-STAT6–dependent deregulation of EGR1-dependent gene expression. In summary, this study establishes a potential molecular biologic basis for clinicopathologic differences in SFTs with distinct NAB2-STAT6 gene fusion variants.
CRIS-Team Scopus Importer:2021-04-02

Inactivating Mutations of RB1 and TP53 Correlate With Sarcomatous Histomorphology and Metastasis/Recurrence in Gastrointestinal Stromal Tumors - Merten, Larissa; Agaimy, Abbas; Moskalev, Evgeny; Giedl, Josef; Kayser, Claudia; Geddert, Helene; Schaefer, Inga-Marie; Cameron, Silke; Werner, Martin; Stroebel, Philip; Hartmann, Arndt; Haller, Florian (American Journal of Clinical Pathology, 2016)
Loss-of-function mutations in TP53 and CDKN2A have been found at varying frequencies in gastrointestinal stromal tumors (GISTs), while no mutations of RB1 have been reported to date. The aim of the current study was to determine the mutation frequency of TP53, RB1, and CDKN2A in GISTs.A cohort of 83 primary untreated GISTs was analyzed for mutations in TP53, RB1, and CDKN2A by massive parallel sequencing. Tumors with mutations in TP53 and RB1 were analyzed by fluorescence in situ hybridization for the corresponding gene loci.Two GISTs harbored inactivating mutations in RB1, and two other GISTs displayed inactivating mutations in TP53 All four tumors were KIT mutant high-risk tumors with highly cellular sarcomatous histomorphology and variable combinations of plump spindle cells to epithelioid highly atypical cells and high mitotic activity. Three of these patients developed recurrent or metastatic disease, while the fourth patient showed tumor rupture intraoperatively. The combined overall frequency of TP53 and RB1 mutations was 13% considering high-risk or malignant GISTs.TP53 and RB1 mutations seem to be restricted to high-risk/malignant GISTs and occur at an equal although relatively low frequency.
EVALuna2:6897

Intraductal Papillary Mucinous Neoplasms of Minor Salivary Glands With AKT1 p.Glu17Lys Mutation - Agaimy, Abbas; Müller, Susanna; Bumm, Klaus; Iro, Heinrich; Moskalev, Evgeny; Hartmann, Arndt; Stoehr, Robert; Haller, Florian (American Journal of Surgical Pathology, 2018)
The spectrum of low-grade intraductal papillary proliferations of the salivary glands is heterogenous, and reproducible morphologic diagnostic criteria have not yet been established. Recognized types are sialadenoma papilliferum, inverted ductal papilloma, and intraductal papilloma, but some lesions have been possibly included in the morphologic spectrum of cystadenoma or low-grade intraductal carcinomas. We herein present detailed morphologic, immunophenotypic, and genotypic features of 3 minor salivary gland neoplasms affecting 2 men (aged 65 and 71 y) and 1 woman (aged 78 y). They ranged in size from 1 to 2.5 cm. All tumors showed atypical papillary intraductal growth that presented either as uninodular/unicystic lesions (intraductal papilloma-like; n=2) or as a discontinuous growth along the ductal system in a manner similar to pancreatic intraductal papillary mucinous neoplasm (n=1). Variable cytologic and architectural atypia was observed, ranging from bland intraductal papilloma-like features, to areas mimicking atypical ductal hyperplasia and low-grade ductal carcinoma in situ of the breast. Amplicon-based massive parallel sequencing revealed an identical AKT1 p.Glu17Lys mutation in all 3 cases, but absence of concurring mutations in other genes of the RAS or PI3K pathway. This small series represents the first genetic study on salivary intraductal papillary neoplasms. Our cases showed significant variation in the degree of cytologic and architectural atypia, which overlaps with intraductal papillomas at the one end and with low-grade intraductal carcinoma at the other end of the spectrum, suggesting a disease continuum. As the full biological and morphologic characteristics of these ductal papillary lesions remain to be defined, the noncommitted term "intraductal papillary neoplasms" might be more appropriate. Our novel genetic findings mirror similar activating mutations of AKT1 and other PI3K pathway members in intraductal papillary lesions of the breast and anogenital glands.
EVALuna2:34605

Lipomatous Solitary Fibrous Tumors Harbor Rare NAB2-STAT6 Fusion Variants and Show Up-Regulation of the Gene PPARG, Encoding for a Regulator of Adipocyte Differentiation - Haller, Florian; Schlieben, Lea D.; Ferrazzi, Fulvia; Michal, Michael; Stöhr, Robert; Moskalev, Evgeny; Bieg, Matthias; Bovée, Judith V.M.G.; Ströbel, Philip; Ishaque, Naveed; Grützmann, Robert; Meidenbauer, Norbert; et al. (American Journal of Pathology, 2021)
Solitary fibrous tumors (SFTs) harbor activating NAB2-STAT6 gene fusions. Different variants of the NAB2-STAT6 gene fusion have been associated with distinct clinicopathologic features. Lipomatous SFTs are a morphologic variant of SFTs, characterized by a fat-forming tumor component. Our aim was to evaluate NAB2-STAT6 fusion variants and to further study the molecular genetic features in a cohort of lipomatous SFTs. A hybrid-capture–based next-generation sequencing panel was employed to detect NAB2-STAT6 gene fusions at the RNA level. In addition, the RNA expression levels of 507 genes were evaluated using this panel, and were compared with a control cohort of nonlipomatous SFTs. Notably, 5 of 11 (45%) of lipomatous SFTs in the current series harbored the uncommon NAB2 exon 4–STAT6 exon 4 gene fusion variant, which is observed in only 0.9% to 1.4% of nonlipomatous SFTs. Furthermore, lipomatous SFTs displayed significant differences in gene expression compared with their nonlipomatous counterparts, including up-regulation of the gene peroxisome proliferator activated receptor-γ (PPARG). Peroxisome proliferator activated receptor-γ is a nuclear receptor regulating adipocyte differentiation, providing a possible explanation for the fat-forming component in lipomatous SFTs. In summary, the current study provides a possible molecular genetic basis for the distinct morphologic features of lipomatous SFTs.
CRIS-Team Scopus Importer:2021-06-04

Long noncoding RNA HOTAIR is upregulated in an aggressive subgroup of gastrointestinal stromal tumors (GIST) and mediates the establishment of gene-specific DNA methylation patterns - Bure, Irina; Geer, Sandra; Knopf, Jasmin; Roas, Maike; Henze, Sabine; Stroebel, Philipp; Agaimy, Abbas; Wiemann, Stefan; Hoheisel, Joerg D.; Hartmann, Arndt; Haller, Florian; Moskalev, Evgeny (Genes Chromosomes & Cancer, 2018)
Aberrant alterations of DNA methylation are common events in oncogenesis. The origin of cancer-associated epigenetic defects is of interest for mechanistic understanding of malignant transformation and-in the long run-therapeutic modulation of DNA methylation in a locus-specific manner. Given the ability of certain long noncoding RNAs to operate as an interface between DNA and the epigenetic modification machinery which can interact with DNA methyltransferases, we hypothesized-considering HOTAIR as an example-that this transcript may contribute to gene specificity of DNA methylation. Using gastrointestinal stromal tumors (GISTs, n = 67) as a model, we confirmed upregulation of HOTAIR in tumors with high risk of recurrence and showed high abundance of the transcript in GIST cell lines. HOTAIR knockdown in GIST-T1 cells triggered transcriptional response of genes involved in the organization and disassembly of the extracellular matrix and, notably, induced global locus-specific alterations of DNA methylation patterns. Hypomethylation was induced at a total of 507 CpG sites, whereas 382 CpG dinucleotides underwent gain of methylation upon HOTAIR depletion. Importantly, orchestrated gain or loss of methylation at multiple individual CpG sites was shown for cancer-related DPP4, RASSF1, ALDH1A3, and other targets. Collectively, our data indicate that HOTAIR enables target specificity of DNA methylation in GIST and is capable of dual (hypo- and hypermethylation) regulation by a yet to be defined mechanism. The results further suggest the feasibility of manipulating DNA methylation in a targeted manner and are of interest in the context of epigenetic cancer therapy.
EVALuna2:34849

Low-grade Endometrioid Stromal Sarcoma of the Paratestis: A Novel Report With Molecular Confirmation of JAZF1/SUZ12 Translocation - Agaimy, Abbas; Moskalev, Evgeny; Weisser, Wera; Bach, Thorsten; Haller, Florian; Hartmann, Arndt (American Journal of Surgical Pathology, 2018)
Tumors with Müllerian-like serous or mucinous phenotypes originating in the testis and its adnexa are rare neoplasms that have been increasingly recognized in recent years. Cystadenomas with or without ovarian-type stroma, borderline tumors, and adenocarcinomas are the main documented types. Although a handful cases of putative endometrioid adenocarcinomas have been reported, to our knowledge no case of endometrial stromal-type neoplasm has ever been reported in the literature. A 59-year-old man presented with a 2 cm left intrascrotal mass that was found on sonographic examination to arise from the epididymal tail with prominent vascularization. He was otherwise healthy without significant clinical history, endocrinopathy, or external hormone therapy. His testicular tumor markers (beta-HCG, AFP) were normal. Histologic examination of the resection showed a multinodular tumor closely associated with the epididymis and composed of monotonous rounded to ovoid cells with scanty cytoplasm and prominent spiral-like arterioles and capillaries. Mitotic activity was high. No other tumor component was seen. Immunohistochemistry revealed strong and diffuse expression of vimentin, CD10, estrogen receptor, and progesterone receptor. Molecular examination (performed on paraffin-embedded tumor tissue using a 517 gene fusion next-generation sequencing assay) showed a JAZF1/SUZ12 translocation, which was then confirmed by fluorescence in situ hybridization (FISH). These findings are consistent with a low-grade endometrioid stromal sarcoma originating in the paratestis. This report represents a novel addition to the growing spectrum of Müllerian-analog testicular adnexal neoplasms.
EVALuna2:34099

Machine Learning-Supported Diagnosis of Small Blue Round Cell Sarcomas Using Targeted RNA Sequencing. - Schlieben, Lea D.; Carta, Maria Giulia; Moskalev, Evgeny; Stöhr, Robert; Metzler, Markus; Besendörfer, Manuel; Meidenbauer, Norbert; Semrau, Sabine; Janka, Rolf Matthias; Grützmann, Robert; Wiemann, Stefan; Hartmann, Arndt; et al. (Journal of Molecular Diagnostics, 2024)
Small blue round cell sarcomas (SBRCSs) are a heterogeneous group of tumors with overlapping morphologic features but markedly varying prognosis. They are characterized by distinct chromosomal alterations, particularly rearrangements leading to gene fusions, whose detection currently represents the most reliable diagnostic marker. Ewing sarcomas are the most common SBRCSs, defined by gene fusions involving EWSR1 and transcription factors of the ETS family, and the most frequent non-EWSR1-rearranged SBRCSs harbor a CIC rearrangement. Unfortunately, currently the identification of CIC::DUX4 translocation events, the most common CIC rearrangement, is challenging. Here, we present a machine-learning approach to support SBRCS diagnosis that relies on gene expression profiles measured via targeted sequencing. The analyses on a curated cohort of 69 soft-tissue tumors showed markedly distinct expression patterns for SBRCS subgroups. A random forest classifier trained on Ewing sarcoma and CIC-rearranged cases predicted probabilities of being CIC-rearranged >0.9 for CIC-rearranged-like sarcomas and <0.6 for other SBRCSs. Testing on a retrospective cohort of 1335 routine diagnostic cases identified 15 candidate CIC-rearranged tumors with a probability >0.75, all of which were supported by expert histopathologic reassessment. Furthermore, the multigene random forest classifier appeared advantageous over using high ETV4 expression alone, previously proposed as a surrogate to identify CIC rearrangement. Taken together, the expression-based classifier can offer valuable support for SBRCS pathologic diagnosis.
EVALuna2:565265

Mutation status of the mediator complex subunit 12 (MED12) in uterine leiomyomas and concurrent/metachronous multifocal peritoneal smooth muscle nodules (leiomyomatosis peritonealis disseminata) - Rieker, Ralf; Agaimy, Abbas; Moskalev, Evgeny; Hebele, Simone; Hein, Alexander; Mehlhorn, Grit; Beckmann, Matthias; Hartmann, Arndt; Haller, Florian (Pathology, 2013)
Aims: The pathogenesis and classification of multicentric smooth muscle tumours with benign appearance and concurrent/metachronous uterine and peritoneal involvement is controversial and may on occasion be diagnostically challenging. Leiomyomatosis peritonealis disseminata (LPD) is a rare condition affecting women of reproductive age, characterised by the occurrence of multiple small peritoneal smooth muscle nodules with bland histology. Methods: We investigated a total of 12 uterine and seven concurrent/metachronous peritoneal smooth muscle nodules with benign appearance from two females for mutations in the mediator complex subunit 12 (MED12), which has recently been identified as the most frequent genetic aberration in uterine leiomyomas. Results: The first case harboured different MED12 mutations in the peritoneal nodules. Mutational status of peritoneal nodules was discordant with that of the uterine leiomyomas. The second case displayed the same MED12 mutation in all five peritoneal nodules, but this mutation was not detected in her current uterine leiomyomas. Conclusions: Our results suggest that smooth muscle neoplasms with benign appearance of the primary and secondary mü llerian system share a similar genetic background of MED12 mutation in combination with oestrogen dependency. Analysis of MED12 mutation status might be a valuable adjunct tool for the future classification of these sometimes diagnostically challenging multicentric tumours. © 2013 Royal College of Pathologists of Australasia.
CRIS-Team Scopus Importer:2021-07-19
Keywords: Leiomyomatosis peritonealis disseminata; MED12; Uterine leiomyoma

NAB2::STAT6 fusions and genome-wide DNA methylation profiling: Predictors of patient outcomes in meningeal solitary fibrous tumors - Eschbacher, Kathryn L.; Tran, Quynh T.; Moskalev, Evgeny; Jenkins, Sarah; Fritchie, Karen; Stöhr, Robert; Caron, Alissa; Link, Michael J.; Brown, Paul D.; Guajardo, Andrew; Brat, Daniel J.; Wu, Ashley; et al. (Brain Pathology, 2024)
Meningeal solitary fibrous tumors (SFT) are rare and have a high frequency of local recurrence and distant metastasis. In a cohort of 126 patients (57 female, 69 male; mean age at surgery 53.0 years) with pathologically confirmed meningeal SFTs with extended clinical follow-up (median 9.9 years; range 15 days–43 years), we performed extensive molecular characterization including genome-wide DNA methylation profiling (n = 80) and targeted TERT promoter mutation testing (n = 98). Associations were examined with NAB2::STAT6 fusion status (n = 101 cases; 51 = ex5-7::ex16-17, 26 = ex4::ex2-3; 12 = ex2-3::exANY/other and 12 = no fusion) and placed in the context of 2021 Central Nervous System (CNS) WHO grade. NAB2::STAT6 fusion breakpoints (fusion type) were significantly associated with metastasis-free survival (MFS) (p = 0.03) and, on multivariate analysis, disease-specific survival (DSS) when adjusting for CNS WHO grade (p = 0.03). DNA methylation profiling revealed three distinct clusters: Cluster 1 (n = 38), Cluster 2 (n = 22), and Cluster 3 (n = 20). Methylation clusters were significantly associated with fusion type (p < 0.001), with Cluster 2 harboring ex4::ex2-3 fusion in 16 (of 20; 80.0%), nearly all TERT promoter mutations (7 of 8; 87.5%), and predominantly an “SFT” histologic phenotype (15 of 22; 68.2%). Clusters 1 and 3 were less distinct, both dominated by tumors having ex5-7::ex16-17 fusion (respectively, 25 of 33; 75.8%, and 12 of 18; 66.7%) and with variable histological phenotypes. Methylation clusters were significantly associated with MFS (p = 0.027), but not overall survival (OS). In summary, NAB2::STAT6 fusion type was significantly associated with MFS and DSS, suggesting that tumors with an ex5::ex16-17 fusion may have inferior patient outcomes. Methylation clusters were significantly associated with fusion type, TERT promoter mutation status, histologic phenotype, and MFS.
CRIS-Team Scopus Importer:2024-04-12
Keywords: CNS WHO grade; meningeal solitary fibrous tumor; NAB2::STAT6; solitary fibrous tumor; TERT

NAB2-STAT6 Gene Fusion in Meningeal Hemangiopericytoma and Solitary Fibrous Tumor - Fritchie, Karen J.; Jin, Long; Rubin, Brian P.; Burger, Peter C.; Jenkins, Sarah M.; Barthelmeß, Sarah; Moskalev, Evgeny; Haller, Florian; Oliveira, Andre M.; Giannini, Caterina (Journal of Neuropathology and Experimental Neurology, 2016)
Meningeal solitary fibrous tumor (SFT) and hemangiopericytoma (HPC) are considered to be distinct entities in the WHO Classification of CNS Tumours (2007). They harbor NAB2-STAT6 fusions similar to their soft tissue counterparts, supporting the view that they are part of a tumor continuum. We examined 30 meningeal-based tumors originally diagnosed as either SFT or HPC. These showed a spectrum of morphologic features and were diagnosed as SFTs, malignant SFTs, HPCs, or tumors with "intermediate" features. All of the tumors showed nuclear expression of STAT6. SFTs consistently expressed diffuse CD34, while HPCs and intermediate tumors had heterogeneous staining. NAB2-STAT6 fusions were identified in 20 cases, including 7 with exon 4-exon 3, 9 with exon 6-exon 17, and 4 with exon 6-exon 18 fusions. NAB2 exon 4-STAT6 exon 3 fusion correlated with classic SFT morphology and older age and showed a trend toward less mitotic activity; there was also a trend toward more aggressive behavior in tumors lacking NAB2 exon 4-STAT6 exon 3. Thus, despite their clinical and morphologic differences, meningeal-based SFTs, HPCs, and tumors with intermediate features, similar to their soft tissue counterparts, form a histopathologic spectrum unified by STAT6 immunoexpression and NAB2-STAT6 fusion.
EVALuna2:6771

Nuclear NR4A2 (Nurr1) Immunostaining is a Novel Marker for Acinic Cell Carcinoma of the Salivary Glands Lacking the Classic NR4A3 (NOR-1) Upregulation - Haller, Florian; Moskalev, Evgeny; Kuck, Sarina; Bieg, Matthias; Winkelmann, Christa; Müller, Susanna; Ihrler, Stephan; Märkl, Bruno; Eils, Roland; Wiemann, Stefan; Iro, Heinrich; Hartmann, Arndt; et al. (American Journal of Surgical Pathology, 2020)
CRIS-Team Scopus Importer:2020-05-22

Nuclear NR4A3 Immunostaining Is a Specific and Sensitive Novel Marker for Acinic Cell Carcinoma of the Salivary Glands - Haller, Florian; Skálová, Alena; Ihrler, Stephan; Märkl, Bruno; Bieg, Matthias; Moskalev, Evgeny; Erber, Ramona; Blank, Susanne; Winkelmann, Christa; Hebele, Simone; Baněčková, Martina; Wiemann, Stefan; et al. (American Journal of Surgical Pathology, 2019)
Recently, we discovered the recurrent genomic rearrangement [t(4;9)(q13;q31)] enabling upregulation of the transcription factor Nuclear Receptor Subfamily 4 Group A Member 3 (NR4A3) through enhancer hijacking as the oncogenic driver event in acinic cell carcinoma (AciCC) of the salivary glands. In the current study, we evaluated the usefulness of NR4A3 immunostaining and NR4A3 fluorescence in situ hybridization (FISH) in the differential diagnosis of AciCC, comparing a total of 64 AciCCs including 17% cases with high-grade transformation, 29 secretory (mammary analog) carcinomas (MASC), and 70 other salivary gland carcinomas. Nuclear NR4A3 immunostaining was a highly specific (100%) and sensitive (98%) marker for AciCC with only 1 negative case, whereas NR4A3 FISH was less sensitive (84%). None of the MASCs or other salivary gland carcinomas displayed any nuclear NR4A3 immunostaining. The recently described HTN3-MSANTD3 gene fusion was observed in 4 of 49 (8%) evaluable AciCCs, all with nuclear NR4A3 immunostaining. In summary, NR4A3 immunostaining is a highly specific and sensitive marker for AciCC, which may be especially valuable in cases with high-grade transformation and in "zymogen granule"-poor examples within the differential diagnostic spectrum of AciCC and MASC.
CRIS-Team Scopus Importer:2019-09-03
Keywords: acinic cell carcinoma; HTN3-MSANTD3; immunohistochemistry; NR4A3; salivary glands; translocation

Paediatric and adult soft tissue sarcomas with NTRK1 gene fusions: a subset of spindle cell sarcomas unified by a prominent myopericytic/haemangiopericytic pattern - Haller, Florian; Knopf, Jasmin; Ackermann, Andreas; Bieg, Matthias; Kleinheinz, Kortine; Schlesner, Matthias; Moskalev, Evgeny; Will, Rainer; Satir, Ali Abdel; Abdelmagid, Ibtihalat E.; Giedl, Josef; Carbon, Roman; et al. (Journal of Pathology, 2016)
Neoplasms with a myopericytomatous pattern represent a morphological spectrum of lesions encompassing myopericytoma of the skin and soft tissue, angioleiomyoma, myofibromatosis/infantile haemangiopericytoma and putative neoplasms reported as malignant myopericytoma. Lack of reproducible phenotypic and genetic features of malignant myopericytic neoplasms have prevented the establishment of myopericytic sarcoma as an acceptable diagnostic category. Following detection of a LMNA-NTRK1 gene fusion in an index case of paediatric haemangiopericytoma-like sarcoma by combined whole-genome and RNA sequencing, we identified three additional sarcomas harbouring NTRK1 gene fusions, termed 'spindle cell sarcoma, NOS with myo/haemangiopericytic growth pattern'. The patients were two children aged 11 months and 2 years and two adults aged 51 and 80 years. While the tumours of the adults were strikingly myopericytoma-like, but with clear-cut atypical features, the paediatric cases were more akin to infantile myofibromatosis/haemangiopericytoma. All cases contained numerous thick-walled dysplastic-like vessels with segmental or diffuse nodular myxohyaline myo-intimal proliferations of smooth muscle actin-positive cells, occasionally associated with thrombosis. Immunohistochemistry showed variable expression of smooth muscle actin and CD34, but other mesenchymal markers, including STAT6, were negative. This study showed a novel variant of myo/haemangiopericytic sarcoma with recurrent NTRK1 gene fusions. Given the recent introduction of a novel therapeutic approach targeting NTRK fusion-positive neoplasms, recognition of this rare but likely under-reported sarcoma variant is strongly encouraged.
EVALuna2:6792

Phenotypical and molecular distinctness of sinonasal haemangiopericytoma compared to solitary fibrous tumour of the sinonasal tract - Agaimy, Abbas; Barthelmeß, Sarah; Geddert, Helene; Boltze, Carsten; Moskalev, Evgeny; Koch, Michael; Wiemann, Stefan; Hartmann, Arndt; Haller, Florian (Histopathology, 2014)
Sinonasal haemangiopericytoma (SN-HPC) is a rare sinonasal mesenchymal neoplasm of perivascular myoid cell origin. Solitary fibrous tumour (SFT) occurs only very rarely in the sinonasal tract. SFT and soft tissue HPC have been considered a single entity. Recently, recurrent gene fusions involving NAB2-STAT6 resulting in differential expression of STAT6 were characterized as central molecular events in SFT. However, no data exist for NAB2-STAT6 status or STAT6 expression in SN-HPC.We examined six SN-HPCs and two sinonasal SFTs by immunohistochemistry and RT-PCR for NAB2-STAT6 fusions. SN-HPC affected three females and three males (mean age: 72 years). They expressed smooth muscle actin, lacked strong CD34 reactivity and were negative for nuclear STAT6 expression. RT-PCR analysis confirmed the absence of NAB2-STAT6 fusions in all cases. Conversely, both sinonasal SFTs (in males aged 39 and 52 years) displayed classical features of pleuropulmonary and soft-tissue SFTs (uniformly CD34-positive with strong nuclear expression of STAT6). RT-PCR revealed NAB2-STAT6 fusions in both cases.These findings confirm the molecular and phenotypical distinctness of these two entities. While SN-HPC is a site-specific sinonasal neoplasm of as yet unknown molecular pathogenesis, sinonasal SFTs show phenotypical and molecular identity to their pleural/extrapleural counterparts.
EVALuna2:6649

Recurrent Mutations within the Amino-Terminal Region of ?-Catenin Are Probable Key Molecular Driver Events in Sinonasal Hemangiopericytoma - Haller, Florian; Bieg, Matthias; Moskalev, Evgeny; Barthelmeß, Sarah; Geddert, Helene; Boltze, Carsten; Diessl, Nicolle; Braumandl, Karin; Brors, Benedikt; Iro, Heinrich; Hartmann, Arndt; Wiemann, Stefan; et al. (American Journal of Pathology, 2015)
Sinonasal hemangiopericytoma (SN-HPC) is an uncommon, site-specific, low-grade mesenchymal neoplasm of probable perivascular myoid cell origin. In contrast to solitary fibrous tumors of soft tissue and sinonasal tract origin, SN-HPCs were recently shown to lack recurrent NAB2-STAT6 fusion variants. Other molecular alterations known to occur in some of soft tissue perivascular myoid cell neoplasms were also absent in SN-HPC; thus, the molecular pathogenesis of SN-HPCs remained unknown. Guided by whole-genome sequencing combined with RNA sequencing of an index case, we analyzed a total of six SN-HPCs for mutations within the amino-terminal region of the gene CTNNB1 (cadherin-associated protein), ? 1, 88 kDa, encoding ?-catenin. All six cases showed missense mutations, with amino acid substitutions clustering at positions 33 to 45, corresponding to the recognition site of the ?-catenin destruction complex. Similar CTNNB1 mutations have been described in a variety of epithelial and mesenchymal neoplasms. These mutations prevent ?-catenin phosphorylation and proteasomal degradation but promote its nuclear accumulation and subsequent increased transcription of Wingless-related integration site target genes. Consistent with these molecular findings, ?-catenin IHC showed consistent diffuse and strong nuclear staining of the tumor cells in all six SN-HPCs. Our results highlight, for the first time, CTNNB1 mutations as the likely initiating molecular events driving SN-HPC tumorigenesis, which places SN-HPC among the growing family of ?-catenin-driven mesenchymal neoplasms.
EVALuna2:6646

Recurrent Somatic PDGFRB Mutations in Sporadic Infantile/Solitary Adult Myofibromas But Not in Angioleiomyomas and Myopericytomas - Agaimy, Abbas; Bieg, Matthias; Michal, Michael; Geddert, Helene; Maerkl, Bruno; Seitz, Jan; Moskalev, Evgeny; Schlesner, Matthias; Metzler, Markus; Hartmann, Arndt; Wiemann, Stefan; Michal, Michal; et al. (American Journal of Surgical Pathology, 2017)
Infantile myofibroma (MF) is an uncommon benign myofibroblastic tumor of infancy and childhood. Solitary adult MF shares similar features with infantile MF. The lesions occur in 3 clinicopathologic settings: solitary, multicentric, and generalized and can be either sporadic or familial. Traditionally, infantile MF has been included in the spectrum of infantile hemangiopericytoma. The recent World Health Organization classification listed MF, angioleiomyoma, and myopericytoma under the general heading of perivascular tumors in the sense of a morphologic spectrum of perivascular myoid cell neoplasms. Although activating germline PDGFRB mutations have recently been linked to familial infantile MF, the molecular pathogenesis of sporadic infantile and adult solitary MF remained unclear. In this study, we analyzed 25 solitary MFs without evidence of familial disease (9 infantile and 16 adult MFs) to address the question whether somatic PDGFRB mutations might be responsible for the sporadic form of the disease. Given the presumed histogenetic link of MF to myopericytoma and angioleiomyoma, we additionally analyzed a control group of 6 myopericytomas and 9 angioleiomyomas for PDGFRB mutations. We detected PDGFRB mutations in 6/8 (75%) analyzable infantile and in 11/16 (69%) adult MFs but in none of the angioleiomyomas or myopericytomas. In 2 infantile MFs, additional sequencing of the germline confirmed the somatic nature of PDGFRB mutations. To our knowledge, this is the first study reporting apparently somatic recurrent PDGFRB mutations as molecular driver events in the majority of sporadic infantile and adult solitary MFs. Our results suggest molecular distinctness of MF as compared with angioleiomyoma/myopericytoma. Investigation of more cases including those with atypical and worrisome features, as well as other mimickers in the heterogenous morphologic spectrum of MF, is mandatory for validating the potential diagnostic value of PDGFRB mutation testing as a possible surrogate in difficult-to-classify lesions.
EVALuna2:6839

Sensitive and specific detection of EML4-ALK rearrangements in non-small cell lung cancer (NSCLC) specimens by multiplex amplicon RNA massive parallel sequencing - Moskalev, Evgeny; Frohnauer, Judith; Merkelbach-Bruse, Sabine; Schildhaus, Hans-Ulrich; Dimmler, Arno; Schubert, Thomas; Boltze, Carsten; Koenig, Helmut; Fuchs, Florian; Sirbu, Horia; Rieker, Ralf J.; Agaimy, Abbas; et al. (Lung Cancer, 2014)
Recurrent gene fusions of anaplastic lymphoma receptor tyrosine kinase (ALK) and echinoderm microtubule-associated protein-like 4 (EML4) have been recently identified in 5% of non-small cell lung cancers (NSCLCs) and are targets for selective tyrosine kinase inhibitors. While fluorescent in situ hybridization (FISH) is the current gold standard for detection of EML4-ALK rearrangements, several limitations exist including high costs, time-consuming evaluation and somewhat equivocal interpretation of results. In contrast, targeted massive parallel sequencing has been introduced as a powerful method for simultaneous and sensitive detection of multiple somatic mutations even in limited biopsies, and is currently evolving as the method of choice for molecular diagnostic work-up of NSCLCs.We developed a novel approach for indirect detection of EML4-ALK rearrangements based on 454 massive parallel sequencing after reverse transcription and subsequent multiplex amplification (multiplex ALK RNA-seq) which takes advantage of unbalanced expression of the 5' and 3' ALK mRNA regions. Two lung cancer cell lines and a selected series of 32 NSCLC samples including 11 cases with EML4-ALK rearrangement were analyzed with this novel approach in comparison to ALK FISH, ALK qRT-PCR and EML4-ALK RT-PCR.The H2228 cell line with known EML4-ALK rearrangement showed 171 and 729 reads for 5' and 3' ALK regions, respectively, demonstrating a clearly unbalanced expression pattern. In contrast, the H1299 cell line with ALK wildtype status displayed no reads for both ALK regions. Considering a threshold of 100 reads for 3' ALK region as indirect indicator of EML4-ALK rearrangement, there was 100% concordance between the novel multiplex ALK RNA-seq approach and ALK FISH among all 32 NSCLC samples.Multiplex ALK RNA-seq is a sensitive and specific method for indirect detection of EML4-ALK rearrangements, and can be easily implemented in panel based molecular diagnostic work-up of NSCLCs by massive parallel sequencing.
EVALuna2:1847

SMARCA4-deficient pulmonary adenocarcinoma: clinicopathological, immunohistochemical, and molecular characteristics of a novel aggressive neoplasm with a consistent TTF1neg/CK7pos/HepPar-1pos immunophenotype - Agaimy, Abbas; Fuchs, Florian; Moskalev, Evgeny; Sirbu, Horia; Hartmann, Arndt; Haller, Florian (Virchows Archiv, 2017)
Alterations in SMARCA4, a member of the chromatin remodeling Switch Sucrose Non-Fermentable (SWI/SNF) complex, characterize a subset of non-small cell lung cancer (NSCLC), but detailed morphological and immunophenotypic description of this tumor type is lacking. We describe 20 NSCLC cases found on routine screening not to express SMARCA4 by immunohistochemistry (IHC). These tumors were stained for CK7, TTF1, SMARCA2, SMARCA4, SMARCB1, and HepPar-1 and analyzed for molecular alterations, using a 160 cancer-related gene panel including the full coding sequence of SMARCA4. Patients were eight females and 12 males aged 41 to 76 (median, 60). Of 18 tumors with detailed data, 14 presented with synchronous distant metastases (M1). Histological examination showed predominantly solid adenocarcinoma (n = 15), frankly rhabdoid (n = 3) and mucinous (n = 2) patterns. Except for the rhabdoid cases, all tumors showed at least focal unequivocal glands and lacked squamous differentiation, justifying a diagnosis of adenocarcinoma. IHC showed a distinctive uniform immunophenotype (CK7+/HepPar-1+/TTF1-) in 18/20 cases. Only 2/16 cases showed limited weak expression of neuroendocrine markers. EGFR mutations and EML4-ALK and ROS1 gene rearrangements were not found in any of the examined cases. Next-generation sequencing, using a 160 cancer-related gene panel, revealed concurrent SMARCA4 and TP53 mutations in nine of the 12 (75%) successfully tested cases. Our study highlights (1) the morphological diversity of SMARCA4-deficient lung adenocarcinoma, (2) the consistent absence of expression of TTF1 in the presence of expression of HepPar-1, (3) absence of EGFR driver mutations, and (4) frequent inactivating SMARCA4 mutations as underlying mechanism of the observed SMARCA4 protein loss. SMARCA4-deficient pulmonary adenocarcinoma is emerging as a distinctive, albeit phenotypically heterogeneous molecular subgroup of TTF1-negative NSCLC. Uniform HepPar-1 expression in this subset of NSCLC may represent a diagnostic pitfall and merits further studies to explore the mechanisms involved.
EVALuna2:34083

Solitary Fibrous Tumor: Natural History and Prognosis in Accordance with the WHO 2021 Classification of CNS Tumors - Eschbacher, Kathryn; Jenkins, Sarah; Fritchie, Karen; Jensch, Kassandra; Moskalev, Evgeny; Caron, Alissa; Link, Michael; Brown, Paul; Guajardo, Andrew; Brat, Daniel; Wu, Ashley; Santagata, Sandro; et al. (JOURNAL OF NEUROPATHOLOGY AND EXPERIMENTAL NEUROLOGY, 2022)
CRIS-Team WoS Importer:2022-06-03

Solitary fibrous tumors/hemangiopericytomas with different variants of the NAB2-STAT6 gene fusion are characterized by specific histomorphology and distinct clinicopathological features - Barthelmeß, Sarah; Geddert, Helene; Boltze, Carsten; Moskalev, Evgeny; Bieg, Matthias; Sirbu, Horia; Brors, Benedikt; Wiemann, Stefan; Hartmann, Arndt; Agaimy, Abbas; Haller, Florian (American Journal of Pathology, 2014)
Recurrent somatic fusions of the two genes, NGFI-A-binding protein 2 (NAB2) and STAT6, located at chromosomal region 12q13, have been recently identified to be presumable tumor-initiating events in solitary fibrous tumors (SFT). Herein, we evaluated a cohort of 52 SFTs/hemangiopericytomas (HPCs) by whole-exome sequencing (one case) and multiplex RT-PCR (all 52 cases), and identified 12 different NAB2-STAT6 fusion variants in 48 cases (92%). All 52 cases showed strong and diffuse nuclear positivity for STAT6 by IHC. We categorized the fusion variants according to their potential functional effects within the predicted fusion protein and found strong correlations with relevant clinicopathological features. Tumors with the most common fusion variant, NAB2ex4-STAT6ex2/3, corresponded to classic pleuropulmonary SFTs with diffuse fibrosis and mostly benign behavior and occurred in older patients (median age, 69 years). In contrast, tumors with the second most common fusion variant, NAB2ex6-STAT6ex16/17, were found in much younger patients (median age, 47 years) and represented typical HPCs from deep soft tissue with a more aggressive phenotype and clinical behavior. In summary, these molecular genetic findings support the concept that classic pleuropulmonary SFT and deep-seated HPC are separate entities that share common features but correlate to different clinical outcome.
EVALuna2:6577

SST gene hypermethylation acts as a pan-cancer marker for pancreatic ductal adenocarcinoma and multiple other tumors: toward its use for blood-based diagnosis - Manoochehri, Mehdi; Wu, Yenan; Giese, Nathalia A.; Strobel, Oliver; Kutschmann, Stefanie; Haller, Florian; Hoheisel, Joerg D.; Moskalev, Evgeny; Hackert, Thilo; Bauer, Andrea S. (Molecular Oncology, 2020)
Aberrant DNA methylation is often involved in carcinogenesis. Our initial goal was to identify DNA methylation biomarkers associated with pancreatic cancer. A genomewide methylation study was performed on DNA from pancreatic ductal adenocarcinoma (PDAC) and endocrine pancreas tumors. Validation of DNA methylation patterns and concomitant alterations in expression of gene candidates was performed on patient samples and pancreatic cancer cell lines. Furthermore, validation was done on independent data from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO). Finally, droplet digital PCR was employed to detect DNA methylation marks in cell-free (cf) DNA isolated from plasma samples of PDAC patients and cancer-free blood donors. Hypermethylation of the SST gene (encoding somatostatin) and concomitant downregulation of its expression were discovered in PDAC and endocrine tumor tissues while not being present in chronic pancreatitis (inflamed) tissues and normal pancreas. Fittingly, treatment with a somatostatin agonist (octreotide) reduced cell proliferation and migration of pancreatic cancer cells. Diagnostic performance of SST methylation in a receiver operating characteristic curve analysis was 100% and 89% for tissue and plasma samples, respectively. A large body of TCGA and GEO data confirmed SST hypermethylation and downregulation in PDAC and showed a similar effect in a broad spectrum of other tumor entities. SST promoter methylation represents a sensitive and promising molecular, pan-cancer biomarker detectable in tumor tissue, and liquid biopsy samples.
CRIS-Team WoS Importer:2020-04-24

The expression of hematopoietic progenitor cell antigen CD34 is regulated by DNA methylation in a site-dependent manner in gastrointestinal stromal tumours - Bure, Irina; Braun, Alexander; Kayser, Claudia; Geddert, Helene; Schaefer, Inga-Marie; Cameron, Silke; Ghadimi, Michael B.; Stroebel, Philipp; Werner, Martin; Hartmann, Arndt; Wiemann, Stefan; Agaimy, Abbas; et al. (International Journal of Cancer, 2017)
The anatomic site-dependent expression of hematopoietic progenitor cell antigen CD34 is a feature of gastrointestinal stromal tumours (GISTs). The basis for the differential CD34 expression is only incompletely understood. This study aimed at understanding the regulation of CD34 in GISTs and clarification of its site-dependent expression. Two sample sets of primary GISTs were interrogated including 52 fresh-frozen and 134 paraffin-embedded and formalin-fixed specimens. DNA methylation analysis was performed by HumanMethylation450 BeadChip array in three cell lines derived from gastric and intestinal GISTs, and differentially methylated CpG sites were established upstream of CD34. The methylation degree was further quantified by pyrosequencing, and inverse correlation with CD34 mRNA and protein abundance was revealed. The gene's expression could be activated upon induction of DNA hypomethylation with 5-aza-2'-deoxycytidine in GIST-T1 cells. In patient samples, a strong inverse correlation of DNA methylation degree with immunohistochemically evaluated CD34 expression was documented. Both CD34 expression and DNA methylation levels were specific to the tumours' anatomic location and mutation status. A constant decrease in methylation levels was observed ranging from almost 100% hypermethylation in intestinal GISTs from duodenum to hypomethylation in rectum. CD34 was heavily methylated in gastric PDGFRA-mutant GISTs in comparison to hypomethylated KIT-mutant counterparts. Next to CD34 hypermethylation, miR-665 was predicted and experimentally confirmed to target CD34 mRNA in GIST-T1 cells. Our results suggest that CD34 expression in GISTs may undergo a complex control by DNA methylation and miR-665. Differential methylation and expression of CD34 in GISTs along the gastrointestinal tract axis and in tumours that harbour different gain-of-function mutations suggest the origin from different cell populations in the gastrointestinal tract.
EVALuna2:6893

The impact of histopathology and NAB2-STAT6 fusion subtype in classification and grading of meningeal solitary fibrous tumor/hemangiopericytoma - Fritchie, Karen; Jensch, Kassandra; Moskalev, Evgeny; Caron, Alissa; Jenkins, Sarah; Link, Michael; Brown, Paul D.; Rodriguez, Fausto J.; Guajardo, Andrew; Brat, Daniel; Velázquez Vega, José E.; Perry, Arie; et al. (Acta Neuropathologica, 2018)
Meningeal solitary fibrous tumor (SFT)/hemangiopericytoma (HPC) is a rare tumor with propensity for recurrence and metastasis. Although multiple classification schemes have been proposed, optimal risk stratification remains unclear, and the prognostic impact of fusion status is uncertain. We compared the 2016 WHO CNS tumor grading scheme (CNS-G), a three-tier system based on histopathologic phenotype and mitotic count, to the 2013 WHO soft-tissue counterpart (ST-G), a two-tier system based on mitotic count alone, in a cohort of 133 patients [59 female, 74 male; mean age 54 years (range 20-87)] with meningeal SFT/HPC. Tumors were pathologically confirmed through review of the first tumor resection (n = 97), local recurrence (n = 35), or distant metastasis (n = 1). A STAT6 immunostain showed nuclear expression in 132 cases. NAB2-STAT6 fusion was detected in 99 of 111 successfully tested tumors (89%) including the single STAT6 immunonegative tumor. Tumors were classified by CNS-G as grade 1 (n = 43), 2 (n = 41), or 3 (n = 49), and by ST-G as SFT (n = 84) or malignant SFT (n = 49). Necrosis was present in 16 cases (12%). On follow-up, 42 patients had at least one subsequent recurrence or metastasis (7 metastasis only, 33 recurrence only, 2 patients had both). Twenty-nine patients died. On univariate analysis, necrosis (p = 0.002), CNS-G (p = 0.01), and ST-G (p = 0.004) were associated with recurrence-free (RFS) but not overall survival (OS). NAB2-STAT6 fusion type was not significantly associated with RFS or OS, but was associated with phenotype. A modified ST-G incorporating necrosis showed higher correlation with RFS (p = 0.0006) and remained significant (p = 0.02) when considering only the primary tumors. From our data, mitotic rate and necrosis appear to stratify this family of tumors most accurately and could be incorporated in a future grading scheme.
EVALuna2:35233

Use of NGS Gene Panel Analyzes for molecularly targeted System Therapy - Roesch, Johannes; Haller, Florian; Lettmaier, Sebastian; Haderlein, Marlen; Hartmann, Arndt; Moskalev, Evgeny; Tögel, Lars; Putz, Florian; Weissmann, T.; Schubert, P.; Höfler, Daniel; Fietkau, Rainer; et al. (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

Utility of different massive parallel sequencing platforms for mutation profiling in clinical samples and identification of pitfalls using FFPE tissue - Fassunke, Jana; Haller, Florian; Hebele, Simone; Moskalev, Evgeny; Penzel, Roland; Pfarr, Nicole; Merkelbach-Bruse, Sabine; Endris, Volker (International Journal of Molecular Medicine, 2015)
In the growing field of personalised medicine, the analysis of numerous potential targets is becoming a challenge in terms of work load, tissue availability, as well as costs. The molecular analysis of non-small cell lung cancer (NSCLC) has shifted from the analysis of the epidermal growth factor receptor (EGFR) mutation status to the analysis of different gene regions, including resistance mutations or translocations. Massive parallel sequencing (MPS) allows rapid comprehensive mutation testing in routine molecular pathological diagnostics even on small formalin-fixed, paraffin-embedded (FFPE) biopsies. In this study, we compared and evaluated currently used MPS platforms for their application in routine pathological diagnostics. We initiated a first round-robin testing of 30 cases diagnosed with NSCLC and a known EGFR gene mutation status. In this study, three pathology institutes from Germany received FFPE tumour sections that had been individually processed. Fragment libraries were prepared by targeted multiplex PCR using institution-specific gene panels. Sequencing was carried out using three MPS systems: MiSeq(TM), GS Junior and PGM Ion Torrent(TM). In two institutes, data analysis was performed with the platform-specific software and the Integrative Genomics Viewer. In one institute, data analysis was carried out using an in-house software system. Of 30 samples, 26 were analysed by all institutes. Concerning the EGFR mutation status, concordance was found in 26 out of 26 samples. The analysis of a few samples failed due to poor DNA quality in alternating institutes. We found 100% concordance when comparing the results of the EGFR mutation status. A total of 38 additional mutations were identified in the 26 samples. In two samples, minor variants were found which could not be confirmed by qPCR. Other characteristic variants were identified as fixation artefacts by reanalyzing the respective sample by Sanger sequencing. Overall, the results of this study demonstrated good concordance in the detection of mutations using different MPS platforms. The failure with samples can be traced back to different DNA extraction systems and DNA quality. Unknown or ambiguous variations (transitions) need verification with another method, such as qPCR or Sanger sequencing.
EVALuna2:6746